2016
DOI: 10.1111/edt.12270
|View full text |Cite
|
Sign up to set email alerts
|

Influence of enamel matrix derivative on healing of root surfaces after bonding treatment and intentional replantation of vertically fractured roots

Abstract: Running titleHealing of vertically fractured roots replanted with EMDOGAIN Keywords vertical root fracture, enamel matrix derivative, new cementum, root resorption, intentional replantation 1 Abstract Background/Aim: The objectives of this study were to histopathologically evaluate

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…When maintaining the ROF tooth is crucial for the benefit of the patient, several treatment alternatives can be considered, including root amputation or hemisection, apicoectomy that includes sectioning of the fractured root coronally to the fracture line, a replantation procedure, or flap elevation and sealing of the fracture line (Tsesis et al 2015;Sugaya et al 2016).…”
Section: Treatment Alternativesmentioning
confidence: 99%
See 1 more Smart Citation
“…When maintaining the ROF tooth is crucial for the benefit of the patient, several treatment alternatives can be considered, including root amputation or hemisection, apicoectomy that includes sectioning of the fractured root coronally to the fracture line, a replantation procedure, or flap elevation and sealing of the fracture line (Tsesis et al 2015;Sugaya et al 2016).…”
Section: Treatment Alternativesmentioning
confidence: 99%
“…Attempts to repair the fracture following extraction of the fractured tooth and replantation of the tooth in order to preserve ROF teeth have been reported mainly in case reports and small case series (Tsesis et al 2015;Arikan et al 2008;Kawai and Masaka 2002;Hayashi et al 2004;Sugaya et al 2016;Dua and Dua 2015;Nizam et al 2016):…”
Section: Cementation Of the Root Fracture Following Extraction And Rementioning
confidence: 99%
“…More recent reports have used intentional replantation to enable extraoral bonding of teeth with vertical root fractures (Hayashi et al 2002, 2004, Nizam et al 2016, Sugaya et al 2016, Okaguchi et al 2018, Rosen et al 2018) or to treat teeth considered as having a periodontally hopeless prognosis (Hou et al 2016, Solakoglu & Filippi 2017, Saida et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…4 Therefore, avulsed teeth should be treated with an agent that is able to inhibit the resorption after delayed replantation. 6 Enamel matrix derivative is also used to promote periodontal regeneration, and its ability to inhibit the resorption of avulsed teeth in animals and humans has been investigated, [7][8][9] in addition to the topical application of alendronate (a bisphosphonate widely used for the treatment of osteoporosis), which has been shown to inhibit root resorption in an animal model 6 Enamel matrix derivative is also used to promote periodontal regeneration, and its ability to inhibit the resorption of avulsed teeth in animals and humans has been investigated, [7][8][9] in addition to the topical application of alendronate (a bisphosphonate widely used for the treatment of osteoporosis), which has been shown to inhibit root resorption in an animal model …”
Section: Introductionmentioning
confidence: 99%
“…5 Among various agents, sodium fluoride is reportedly useful for the inhibition of root resorption and has been recommended for use in the form of 2.4% sodium fluoride phosphate, acidulated at pH 5.5 for 20 minutes. 6 Enamel matrix derivative is also used to promote periodontal regeneration, and its ability to inhibit the resorption of avulsed teeth in animals and humans has been investigated, [7][8][9] in addition to the topical application of alendronate (a bisphosphonate widely used for the treatment of osteoporosis), which has been shown to inhibit root resorption in an animal model of delayed replantation. 10 Moreover, in a recent study, another bisphosphonate, zoledronate, also demonstrated similar effects on root resorption.…”
Section: Introductionmentioning
confidence: 99%